Narrative Scenes on Medieval Metalwork - Hariz, Mira (2023)
The Seljuqs are a tribe from Oguz origins who came into Central Asia from the Eurasian Steppe1. The Turkic dynasty ruled over the area from 1040 to 11942. They were known for their warfare skills, and eventually their rule spread westward through the Atabegs3. Between the 11th and 13th centuries, the region witnessed political unrest. However, art production under the Seljuqs thrived4. One of the materials of which many objects survived is metalwork. The surfaces of these objects are adorned with various decorative schemes which include, enthronement scenes, court entertainment scenes, hunting scenes, astrological symbols, vegetal motifs, and geometry. Figural representation was widespread, however the appearance of the narrative scene of Bahram Gur and Azadeh on metalwork is unprecedented. Three reasons could be attributed to this occurrence. First, the Seljuqs associated with the story of a heroic Persian King. The Seljuq military men decided to include the story of a heroic King on their metalwork as a resemblance to them. Bahram Gur is a ruler from the Sassanian period5. He is known for his hunting prowess, strength against wild animals, and military power. Second, oral traditions, and the widespread of the story of Bahram Gur facilitated the appearance of the narrative scenes on metalwork from this period. The traveling scholars, poets, artists were part of the Muslim culture, which enhanced exchange of knowledge and information. And the stories of Bahram Gur were widespread in Iran which triggered a high image production in the area6. Consequently, the oral traditions lead to the widespread of the stories of Persian Kings. Third, the appreciation of the Seljuqs of the Persian culture, may have triggered the rendering of the narrative scene of Bahram Gur and Azadeh on their metalwork. The Seljuqs were military commanders who came into Persia to defend territory7. The art produced under their rule reflected the culture of Persia. Moreover, the representation of Bahram Gur on their metalwork could indicate the appreciation of some rulers to the story of a heroic Persian Sassanian King.